Rapid velocity encoded imaging in valvular regurgitation - Elmahdi, Abdelaziz M.; Doyle, Mark W.; Anayiotos, Andreas (My University, 1999)
Breath hold conditions of 20 s were achieved by the TURBO-BRISK-VEC order 5. The calculated regurgitant flow compared favorably with actual flow. Significant time savings were achieved by this method.
Keywords: Hemodynamics; Magnetic resonance imaging; Cardiovascular system